Potential impact of climate change on termite distribution in Africa - Shiday BMA; Nkunika POY; Sileshi, Gudeta W.; French JRJ; Nyeko P; Jain S (Sciencedomain International, 2011)
Termites (Order: Isoptera) constitute an integral component of various ecosystems in Africa. Termites are also amongst the most difficult insects to study because of their cryptic behaviour and natural nesting habitat. There are around 2600 species of termites in 280 genera which have been described worldwide and about 39% of the total termite species are found in Africa. Termite identification is crucial to understanding termite distribution and their relationship to climate change. Some termite species are well known pests of agricultural crops, forest trees, wood products and timber-in-service causing considerable damage in Africa. This review paper attempts to collate information on African termite distribution and climate change and highlights some knowledge gaps. Africa is the origin of the termite family of Macrotermitinae. The paper focuses more on economically important termite species in Africa. The use of traditional identification methods coupled with molecular techniques in resolving some of the challenges in termite distribution with particular reference to climate change in Africa are discussed. There is scant information on published literature on the impact of climate change on termites with particular reference to termite distribution in Africa. However there is anectodal evidence to suggest that African termite species will be affected by changes in the local and global climate.